2019
DOI: 10.1139/cjas-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bruising and mortality of broilers during manual handling, module loading, transport, and lairage

Abstract: Multiple factors can affect the risk of bruising and mortality of broilers during loading, transport, and lairage. The risk factors affecting the percentages of broilers in each load that were “dead-on-arrival” (DOA) or bruised were studied from records provided by a processing plant, by undertaking direct observations during on-farm loading and then carrying out multivariable analyses. Selected loads between 2014 and 2015 from seven producers were included in the study. The median DOA per load was 0.13% (Q1 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…When comparing the UK slaughterhouse to other European countries' establishments, these values were shown to be inferior when compared to countries such as Italy, Germany/Netherlands, and Slovakia, which presented averages of 10.0, 2.2 and 0.52% of injuries, respectively [20,33,37]. The DOA % reported in most studies in Europe was about 0.2% [38]. Some of the variability between studies in which factors were identified as significantly affecting injury and mortality were usually due to differences between methodologies used regarding the range of some variables…”
Section: Dead On Arrivalmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the UK slaughterhouse to other European countries' establishments, these values were shown to be inferior when compared to countries such as Italy, Germany/Netherlands, and Slovakia, which presented averages of 10.0, 2.2 and 0.52% of injuries, respectively [20,33,37]. The DOA % reported in most studies in Europe was about 0.2% [38]. Some of the variability between studies in which factors were identified as significantly affecting injury and mortality were usually due to differences between methodologies used regarding the range of some variables…”
Section: Dead On Arrivalmentioning
confidence: 99%
“…Copyright © Ricardo Lacava Bailone APDV.000685. 8(2).2021 used, for example type of catching, loading, climatic conditions, journey duration, transport procedures, stunning, not to mention the robustness of the multivariable analyses [38].…”
Section: Dead On Arrivalmentioning
confidence: 99%